PENGARUH PEMAKAIAN TEPUNGUMBI TALAS (Xanthosoma sagittifolium) DAN PENAMBAHAN METIONIN DALAM RAN SUM PUYUH PERIODE PERTUMBUHAN - Elfawati Elfawati (State Islamic University of Sultan Syarif Kasim Riau, 2006)
The objective of this study was to know the influence of applying of black radish (Xanthosomtt SlIgittifolium) tuber meal and methionine and interaction of them in the growth period quail ration. The experiment was designed as completely randomized design in factoriaJ mode with 2 factors (levels of black radish tuber meal and methionine) and 4 replications. The result showed that the black radish tuber meal might be applied up to 24